Perempuan Sebagai Modal Sosial Pengawasan Partisipatif di Masyarakat: Studi Implementasi Desa Anti Politik Uang di Kalurahan Sardonoharjo, Kabupaten Sleman - Sevy Kusdianita; Mugi Hartana; Muhammad Zulfikar Arsyad; Yunita Melinda Putri (Jurnal Adhyasta Pemilu, 2022)
Participatory supervision is a surveillance movement that comes from the initiation of society on a voluntary basis. This movement involves all elements of society, including women. Women are also active in political participation, even having the potential to become the driving engine of grassroots movements. Currently, women have been active in the election process, become election participants, election organizers and are in the ranks of election supervision. This paper will discuss the role of women as the driving force of participatory supervision in the Anti-Money Politics Village program in Sardonoharjo Village, Sleman Regency, Yogyakarta Special Region through descriptive research methods and qualitative research types using social capital and participation approaches. The conclusion drawn from this study is that women are the social capital of the core movement in society and play a role in the formation of participatory movement patterns. The pattern of participatory movements carried out by women in the election process in the Village Anti-Money Politics program, has the potential to expand so that more massive participatory supervision is realized.